The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s12035-020-01947-w
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mitochondrial Dysfunction on Dopaminergic Neurons in the Olfactory Bulb and Odor Detection

Abstract: Understanding non-motor symptoms of Parkinson's disease is important in order to unravel the underlying molecular mechanisms of the disease. Olfactory dysfunction is an early stage, non-motor symptom which occurs in 95% of Parkinson's disease patients. Mitochondrial dysfunction is a key feature in Parkinson's disease and importantly contributes to the selective loss of dopaminergic neurons the substantia nigra pars compacta. The olfactory bulb, the first olfactory processing station, also contains dopaminergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…From the physiological point of view, the importance of DA interneurons in olfaction has been demonstrated in mice in which the knocking out of dopamine receptors or transporters leads to decreased ability to discriminate odors (Wilson and Sullivan, 1995;Tillerson et al, 2006;Taylor et al, 2009). A similar result was obtained when mice with genetically induced mitochondrial dysfunction were analyzed and found that the odor discrimination deficit was paralleled by a decrease in the number of small PG-DA neurons (Paß et al, 2020). Evidence of their role in humans comes from several studies in which it is shown that olfaction impairment in Parkinson's disease is one of the first signs of neurodegeneration, even prodromic to motor deficits (Doty, 2012).…”
Section: Physiological Role Of Dopaminergic Neuronsmentioning
confidence: 70%
“…From the physiological point of view, the importance of DA interneurons in olfaction has been demonstrated in mice in which the knocking out of dopamine receptors or transporters leads to decreased ability to discriminate odors (Wilson and Sullivan, 1995;Tillerson et al, 2006;Taylor et al, 2009). A similar result was obtained when mice with genetically induced mitochondrial dysfunction were analyzed and found that the odor discrimination deficit was paralleled by a decrease in the number of small PG-DA neurons (Paß et al, 2020). Evidence of their role in humans comes from several studies in which it is shown that olfaction impairment in Parkinson's disease is one of the first signs of neurodegeneration, even prodromic to motor deficits (Doty, 2012).…”
Section: Physiological Role Of Dopaminergic Neuronsmentioning
confidence: 70%
“…Indeed, new dopamine and calretinin cells are continually integrated during adult neurogenesis ( Ninkovic et al, 2007 ; Adam and Mizrahi, 2011 ). Given that dopaminergic cells process odor cues, the reduction of dopamine neurons, receptors or transporters decreases the capability to discriminate odors ( Taylor et al, 2009 ; Paß et al, 2020 ). On the other hand, calretinin interneurons are responsible for inhibiting noisy excitatory signals that reach mitral/tufted cells ( Capsoni et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that perished SNc dopaminergic neurons or parkinsonian features are further reported in cases of spinocerebellar ataxia ( Palin et al, 2013 ; Tzoulis et al, 2013 ; Synofzik 2019 ) and CMT2A ( Aerts et al, 2016 ), emphasizing their special vulnerability to mitochondrial defects. Cell type intrinsic properties are of critical importance for the high susceptibility of SNc dopaminergic neurons, which is highlighted by other dopamine neuron populations being spared upon mitochondrial dysfunction ( Pass et al, 2020 ; Ricke et al, 2020 ). Thus, a lot of attention is currently paid on voltage-gated Ca 2+ channels, since they present promising pharmacological targets to decrease the cytosolic Ca 2+ burden and its associated pathology, including mitochondrial dysfunction as well as the formation of αSyn aggregates.…”
Section: Discussionmentioning
confidence: 99%